The Movement Of Islamic Fundamentalism The Classical, Pre-Modern And Contemporary - Anshor, Ahmad Muhtadi (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Abstract Religious fundamentalism is understood as an answer of the socialist group and the political elite of the religious in a religious group. So religious fundamentalism is always evolving in the modern era. As a study-based literature, this study will highlight the historical roots of religious fundamentalism in the era of the classical, pre-modern, and contemporary implications in the discovery model the thinking of fundamentalism religious in the contemporary era. The findings in this study show that fundamentalism has a few basic principles. Principles basic principles: the first is oppositional (understand resistance), the second the rejection of hermeneutics, the third rejection of pluralism and relativism, and the fourth is the rejection of the historical development and sociological. By using basic principles such then the movement of the Kharijites, the Wahabi movement in the Arabian peninsula, the movement of Shaykh Uthman and Fodio in Northern Nigeria, the movement Padri in Minangkabau and Al-Ikhwan al-Muslim in Egypt can be categorized in the movement of Islamic fundamentalism. Keywords: Islamic Fundamentalism, classical, pre-modern, contemporary. Abstrak Fundamentalisme agama difahami sebagai sebuah jawaban dari kelompok sosialis dan elit politik keagamaan dalam sebuah kelompok agama. Sehingga fundamentalisme agama ini selalu berkembang dalam era modern saat ini. Sebagai kajian berbasis pustaka, kajian ini akan menyorot akar sejarah fundamentalisme agama pada era klasik, pra-modern, dan kontemporer yang berimplikasi pada penemuan model pemikiran fundamentalisme keagamaan pada era kontemporer. Temuan dalam kajian ini menunjukkan bahwa fundamentalisme memiliki beberapa prinsip dasar. Prinsip-prinsip dasar tersebut: pertama adalah oppositionalism (paham perlawanan), kedua penolakan terhadap hermeneutika, ketiga penolakan terhadap pluralisme dan relativisme, dan keempat adalah penolakan terhadap perkembangan historis dan sosiologis. Dengan menggunakan prinsip-prinsip dasar tersebut maka gerakan kaum Khawarij, gerakan Wahabi di semenanjung Arabia, gerakan Syaikh Usman dan Fodio di Nigeria Utara, gerakan Padri di Minangkabau dan Al-Ikhwan al-Muslimun di Mesir dapat dikategorikan dalam gerakan fundamentalisme Islam. Kata Kunci : Fundamentalisme Islam, klasik, pra-modern, kontemporer.